2020
DOI: 10.1016/j.urolonc.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multicentre study using high intensity focused ultrasound (HIFU) for the focal treatment of prostate cancer: Safety outcomes and complications

Abstract: Purpose To investigate focal therapy using High Intensity Focused Ultrasound (HIFU) for the treatment of localized prostate cancer (CaP), we analyzed the safety and complications of this procedure. Methods Patients (pts) eligible for this multicenter prospective cohort study suffered from low to intermediate risk localized CaP with no prior treatment. After tumor identification on multiparametric MRI and in prostate biopsy, the lesions were treated with HIFU observing a safety margin of 8 to 10 mm. Adverse eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…The most common complications after focal therapy usually occur within the first 30 days after the intervention ( 22 ). These are often haematuria, infectious complications or catheter related issues such as pain, discomfort and urethral sloughing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common complications after focal therapy usually occur within the first 30 days after the intervention ( 22 ). These are often haematuria, infectious complications or catheter related issues such as pain, discomfort and urethral sloughing.…”
Section: Resultsmentioning
confidence: 99%
“…In case of a second failed TWOC a cystoscopy under general anesthesia is advised in order to rule-out the presence of obstructive necrotic tissue that would require a transurethral resection. The need for endoscopic interventions after focal treatments has become less frequent with the advent of more conservative ablation templates ( 22 , 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 847 studies identified, we included 20 in the final analysis (Figure -1): 1 randomised controlled trial (9), 10 prospective development studies (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and 9 retrospective case series (6,(20)(21)(22)(23)(24)(25)(26)(27). Across all the studies, 4209 patients were treated with focal HIFU.…”
Section: Evidenced Synthesismentioning
confidence: 99%
“…HIFU itself has already made an appearance in guidelines, concerning PC treatment options, although only as an investigational therapeutic tool, or as salvage therapy [134]. The most important benefit of HIFU is that it is minimally invasive when compared to surgical treatment, and it is devoid of systemic toxicity in comparison with androgen deprivation therapy (ADT) or chemotherapy, nevertheless possible adverse effects may occur quite frequently, and they include erectile dysfunction, urinary tract infections, rectal injuries, and more [135,136]. Properties of HIFU can be divided into a few groups -ablative and non-ablative (mechanical), immune, and biological effects; induced activity depends on a multitude of factors including frequency, pressure, duty cycle, and treatment time, achieved temperature, tissue susceptibility, and more.…”
Section: High-intensity Focused Ultrasoundmentioning
confidence: 99%